DNA databases as alternative data sources for criminological research - De Moor, Sabine (European journal on criminal policy and research, 2017)
DNA traces found at crime scenes and DNA records held in databases have already helped the police to solve numerous investigations into specific crimes. The police clearly benefit from the use of forensic science at an operational (i.e. case) level. This paper focuses on the use of forensic DNA at a strategic level: its use in the study of patterns of criminal behaviour. The usual sources of information for this type of research are recorded crime data, self-report studies and victimization surveys. However, as our review will show, these data sources cannot provide a complete picture of crime. We therefore propose an alternative approach to criminological research that takes into account DNA databases and has the potential to augment current methods and extend the existing knowledge beyond known offenders. The use of DNA databases has an important advantage for criminological research: it is possible to link offences committed by the same individual, whether the offender’s identity is known or not. By making a one-on-one comparison of police data with the corresponding DNA data, not only can co-offenders be studied, but a larger network of offenders connected to each other can also be analysed, even if their identity is unknown to the police.